ANALISIS FAKTOR STRATEGIK MANAJEMEN SUMBER DAYA MANUSIA UNTUK MENINGKATKAN KINERJA KARYAWAN - Dian Ika Ningrum; Tjiptogoro Dinarjo Soehari (Akademika, 2019)
Improvement employee performance is very important to support company’s business in property industry. Therefore, this research is used as a basic policy to improve employee performance. The methodology in this research is quantitative exploratory method and analyze data used software SPSS for Windows version 24. The variables are Employee Performance (Y) as dependent variable, Work Environment (X1), Competence (X2) and Compensation (X3) as independent variables. This research was conducted at PT Jasamarga Properti with a population of 64 people as saturated samples. All employees are used as samples. (1) Multiple linear regression equation Y = 1.419 + 0.313 X1 + 0.199 X2 + 0.187 X3 + e; Rsquare = 0.759, F = 59.844 (2) The work environment is the most dominant factor in Employee Performance; (3) Competence and Compensation have a significant influence on Employee Performance. The results of Employee Performance are 1,419. If X1, X2 and X3 are considered zero, it will affect employee performance by 1.419 in the Likert scale 1-5. The result is that employee performance is categorized as a very bad category.